PERANCANGAN VISUAL BRANDING PROMOSI WISATA PAINAN KABUPATEN PESISIR SELATAN SUMATERA BARAT - VIKI MAULANA FEBRIANTO, Drs. Suib Awrus, M.Pd., Ir. Drs. Heldi, M.Si., Ph.D. (Universitas Negeri Padang, 2018)
Painan South coastal district located on the coast of this lot save the tourism potential, especially marine tourism. The problem faced is not yet optimal romotion of information communication tourism in Painan. For that need to be built visual branding Painan Tourism identity, visual branding design is aimed at promoting Painan Tour, as well as enhance the image of Painan tourism. This design methodology uses Mind Mapping. While the analytical approach using the SWOT analysis approach to find the strengths, weaknesses, opportunities, and hreats in visual paint branding Painan Tourism.Visual branding Painan tourism is applied to the main media that is manual book, and stationery set. Supporting media in the form of X-Banner, Wall Clock, sticker, keychain, T-shirt, mug, supporting media also serves as a tourism promotion media Painanpromosi wisata Painan.Kata kunci : Visual Branding, Wisata Painan, Pantai Selatan, Desain, Logogram.